Research progress on ANXA5 in recurrent pregnancy loss. (September 2022) - Peng, Liying; Yang, Wanli; Deng, Xujing; Bao, Shihua
Abstract: The incidence of recurrent pregnancy loss (RPL) in fertile women ranges from 1% to 5%, of which about 50% of them are due to unknown causes. The possible pathogenesis of RPL is an urgent problem to be solved in the clinical. Mutations or polymorphisms of certain genes in the coagulation mechanism are associated with susceptibility to thrombotic diseases and are one of the main reasons for the occurrence of RPL. Among them, the ANXA5 gene was newly studied and some single nucleotide polymorphisms (SNPs) in the promoter region of ANXA5 have been reported to be associated with RPL in multiple races. In this review, we summarized the research progress on the correlation between the SNPs in ANXA5 and RPL, hoping to provide some valuable guidance for the future studies. Highlights: ANXA5 which is encoded by the ANXA5 gene plays a significant role in the maintenance of pregnancy. The M2/ANXA5 haplotype carriers generate hypercoagulability in intervillous space ultimately resulting in pregnancy loss. Exploring the relationship between the M2 haplotype and aPL antibodies may shed the light for some unexplained RPL patients.